Discrimination among American Indian and Alaska Native people: implications for public health communication - Begay, Rene L.; Roland, Matthew J.; Blair, Irene V.; Brondolo, Elizabeth (Frontiers in Public Health, 2024)
Introduction – American Indian and Alaska Native People (AI/AN) have experienced discrimination stemming from sustained attempts to erase AI/AN People and their culture or livelihood. Research identifying the types of discrimination experienced by AI/AN people is needed to help individuals recognize discrimination in daily life. We examine experiences of discrimination among an urban AI/AN population using a mixed methods approach. Methods – Self-identified AI/AN participants (N = 303, n = 294 with complete data; 63% women, mean age = 43 years) were recruited from the Denver-Metro area in Colorado. Stress and coping models of discrimination guided our analysis. Exposure to discrimination was quantitatively assessed via the Brief Perceived Ethnic Discrimination Questionnaire (BPEDQ), a self-report measure including four subscales assessing workplace discrimination, social exclusion, physical threat and harassment, and stigmatization. Participants responded to a laboratory recall task in which they described an episode of discrimination and their affective and coping responses. Content analysis was conducted on transcribed responses to illustrate discrimination exposure as reported in the BPEDQ and in prior theoretical work on coping with discrimination. Results – Repeated measures analyses revealed participants reported experiencing social exclusion more than other forms of discrimination, followed by reports of workplace discrimination, stigmatization, and physical threat. Consistent with these quantitative findings, participants were more likely to recall experiences of social threat (94%), including episodes of workplace discrimination, social exclusion, and stigmatization than physical threat and harassment. Almost half the participants (47%) reported confronting or directly addressing the discrimination, and 38% reported avoiding a direct approach. For 44% of participants, their predominant emotional response included internalizing emotions such as fear/sadness/embarrassment, and another 44% reported experiencing externalizing emotions, including anger. Conclusion – Our descriptive findings present the experiences of urban AI/AN People who have experienced many forms of unjust and prejudicial treatment. These data can provide useful information to help the general public and AI/AN individuals more readily recognize and prevent discriminatory behavior, and consequently mitigate deleterious effects of discrimination on health.